Factors Influencing Acceptance of Rural Posting by Health Workers to Krachi West District, Volta Region, Ghana - Abiwu, H.A.K. (University of Ghana, 2019)
Introduction: Access to quality healthcare depends on the availability of qualified and adequate healthcare workers; unfortunately, most health workers prefer to work in urban and peri-urban communities to the detriment of those living in rural communities including Krachi West District. Identifying factors influencing acceptance of rural posting and formulating policies based on these factors will improve rural posting acceptance. This study, therefore, investigated factors influencing acceptance of rural posting to Krachi West District. Methods: This was a cross-sectional analytical study which adopted both qualitative and quantitative approaches to data collection. Self-administered structured questionnaires were administered to all health workers at post. Descriptive statistics were performed and statistical significance of various factors and acceptance of rural posting was tested using Chi-square and Fisher’s exact tests. Logistic regression was used to determine the association between the various factors and acceptance of rural posting to Krachi West. Five Focus Group Discussions were held, digitally recorded and transcribed verbatim. The qualitative data were analysed using framework analysis. Results: Though several factors working together determine the willingness of a health worker to accept rural posting to Krachi, the only factor showing statistically significant association with acceptance of rural posting is the attitude of the staff towards working in a rural area (Adjusted OR 9.25; p-value < 0.001). Additionally, health workers received news of posting to Krachi with negative emotions such as sadness, frustration, and feeling of punishment but the process of visiting the district to verify their fears often led to the acceptance of the posting. Conclusion: A health workers’ attitude to working in a rural area is the only statistically significant factor associated with acceptance of rural posting to Krachi West District. Posting to the district is associated with negative emotions but exposure to the district led to acceptance of the posting.
MPH.
Keywords: Rural Posting; Health Workers; Krachi West District; Volta Region; Ghana